The Dichotomy of Poetry and Prose in Arabic Literary Criticism between Classical and Modern Approaches - al hadi, soumia (El Omda in Linguistics and Discourse Analysis, 2023)
The duality of poetry and prose, Is one of the topics that have attracted the attention of ancient and modern Arab critics, as they paid special attention to it and studied the various qualitative differences between the two genres. They made the textual characters of poetry and thus prose. It has taken another turn in the modern and current era. As a result, they have struggled to establish a boundary between them.que the literary genre, becomes a architext, and an transgeneric.